Evaluating foraminifera-bound δ15N as an ocean deoxygenation proxy: the influence of oxygen-deficient zone depths - Tianshu Kong; Thomas Lee; Kameko Landry; Ruixiang Zhai; Sijia Dong; Xingchen Tony Wang (Frontiers in Marine Science, 2025)
The nitrogen isotopic composition of shell-bound organic matter in planktonic foraminifera (FB-δ 15 N) is widely used as a proxy for past ocean deoxygenation because water-column denitrification in oxygen-deficient zones (ODZs; [O 2 ] < 5 µmol/kg) preferentially removes 14 N, enriching the remaining nitrate in 15 N. Typically, increases in FB-δ 15 N records from ODZ-influenced regions are interpreted as evidence of ODZ expansion or intensification. However, planktonic foraminifera predominantly feed on organic nitrogen derived from the subsurface nitrate immediately below the euphotic zone, often above ODZ core depths. It remains unclear if the δ 15 N maxima observed within ODZ cores, reflecting denitrification intensity at a given location, directly correlates with the FB-δ 15 N values recorded above. Here, we combine new and published data from the eastern tropical Pacific ODZs to examine relationships among subsurface nitrate δ 15 N, ODZ δ 15 N maxima, and ODZ upper-boundary depths. Our analysis reveals a strong correlation between subsurface nitrate δ 15 N and ODZ δ 15 N maxima (R 2 = 0.56-0.79), supporting the use of FB-δ 15 N as an indicator of denitrification intensity within ODZ regions. However, subsurface nitrate δ 15 N also correlates strongly with the ODZ upper-boundary depth (R 2 = 0.57-0.59), with lower δ 15 N values observed where ODZs are deeper. For example, at our new study sites in the Eastern Tropical North Pacific (5 – 8°N), where the ODZ upper-boundary depth is ~300 m, the δ 15 N maxima (>10‰) at the ODZ core decrease upward to subsurface nitrate δ 15 N values of ~6.5‰ — only slightly higher than the global pycnocline nitrate δ 15 N. These results suggest that variations in ODZ depth should be accounted for when interpreting FB-δ 15 N records (and other δ 15 N archives) from ODZ regions. Under warmer conditions, organic matter remineralization may become shallower due to the temperature dependence of respiration, shifting ODZs upward and elevating FB-δ 15 N even without changes in denitrification rates. To more robustly reconstruct ODZ history using FB-δ 15 N, we recommend using multiple sites from the ODZ interior to regions beyond their modern boundaries. Cores situated outside modern ODZs, where thermocline nitrate δ¹ 5 N still carries the ODZ signature, are ideal for tracing ODZ expansions and contractions, while cores from within the modern ODZs provide complementary constraints on ODZ intensity and vertical structure.